Agile methodology for the development and implementation of an information system in a service organization (AACINI - International Journal of Industrial Engineering, 2023)
The objective of this work is the development and implementation of an information system in a small service organization in the city of Mar del Plata, Argentina. In a previous stage, by applying the Soft Operational Research methodology, a survey of information and definition of requirements was carried out, where the main needs that the information system should cover were determined. Based on these defined requirements, it is proposed to continue with the system development and implementation process. In a first stage, the evaluation and selection of the system provider is carried out by applying the multicriteria method for decision making Analytical Hierarchy Process. In a second stage, agile methodologies are used to manage the development and implementation of the system jointly with the main actors involved. Given that agile methodologies are especially oriented to the management of small projects, their application was a simple and adequate solution for this case study, allowing to obtain a customized and easy-to-adopt information system.
Keywords: Information system; Agile methodologies; Analytical hierarchy process; Services